UV VISIBLE SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION OF DASATINIB IN BULK AND SOLID DOSAGE FORM - MADUR, SAILI; MATOLE, VINOD; KALSHETTI, MALLINATH (International Journal of Current Pharmaceutical Research, 2020)
Objective: A new, simple, sensitive, precise, reproducible UV visible spectrophotometric method was developed for the determination of Dasatinib in Tablet dosage form with methanol. Methods: The method is based on the formation of a colorlesscomplex. The UV spectrum of Dasatinib in methanol showed maximum wavelength at 248 nm. Beer’s law is valid in the concentration range of 7-35µg/ml. this method was validated for linearity, accuracy, precision, assay, ruggedness and robustness. Results: The method has demonstrated excellent linearity over the range of 7-35µg/ml with the regression equation y = 0.0332x+0.0633 and regression coefficient i.e. r2= 0.9994moreover, the method was found to be highly sensitive with LOD(1.08µg/ml) and LOQ(3.29µg/ml). Conclusion: Based on the results the proposed method can be successfully applied for the assay of Dasatinib in various tablet dosage forms.